An act for transporting and victualing of voluntiers inlisted in this colony to serve in the expedition therein mentioned (Published at the City-Hall of the City of New-York, 1740)
July 12, 1740 act of the Province of New York General Assembly regarding the transportation and victualing of the volunteers to serve in the British expeditions to the West Indies. Much of the act dealt with the funding structure, particularly in borrowing rates, hiring vessels for transportation, establishing commissioners and other steps needed to pay for the expeditions.